Improving the efficiency of self-planing of main results of building enterprises - Krikun, K.; Oliferuk, S.; Ryazanov, A.; Serdiuchenko, N. (Ways to Improve Construction Efficiency, 2019)
The article considers the possibilities of increasing the efficiency of self-planning of the main results of the activity of construction enterprises. In a marketing system of production and management planning is carried out on the basis of the economic mechanism of self-planning, taking into account the state orientation and guiding planning through the development of short-term, medium-term, long-term, as well as strategic in the form of major strategies and specific business plans. The process of effective self-planning is proposed to be carried out by identifying the main areas for increasing the efficiency of activities and developing the main economic indicators. Also presented is a sequence diagram of the process of ensuring the effectiveness of self-planning.